2023
DOI: 10.1111/ibi.13217
|View full text |Cite
|
Sign up to set email alerts
|

Human activities at night negatively impact Little Penguin (Eudyptula minor) numbers and behaviours

Abstract: The presence of humans within the natural environment is increasing worldwide. Assessing the impact of such activities on wildlife is crucial for declining populations where human disturbance adds to existing pressures. Here, we investigated how human activities at night influenced Little Penguin Eudyptula minor numbers and behaviours (specifically return time, number of vocalizations and time spent in vigilance) on Granite Island, a declining population in South Australia, Australia. We combined data from reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
2
1
Order By: Relevance
“…A recent study identified the negative effect of anthropogenic activities, i.e. white light sources, at night on little penguins (Costello & Colombelli Négrel, 2023), but evidences are mixed since other study find the opposite (Rodríguez et al, 2018). Multiple hypotheses could explain the absence of response during the anthropause in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…A recent study identified the negative effect of anthropogenic activities, i.e. white light sources, at night on little penguins (Costello & Colombelli Négrel, 2023), but evidences are mixed since other study find the opposite (Rodríguez et al, 2018). Multiple hypotheses could explain the absence of response during the anthropause in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Our study did not consider what impact just the presence of dogs (but not attacks) might have on little penguin behaviour and how this might influence colony size. For example, in South Australia, Costello and Colombelli‐Négrel (2023) found that fewer little penguins were observed on land at night when dogs were present and that penguins returned to land later at night more often, compared to when dogs were absent.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, some little penguin colonies have decreased around Australia and New Zealand (Dann, 1991(Dann, , 1994Dann et al, 2000;Stevenson & Woehler, 2007;Wiebkin, 2011). Like many other seabirds, human activities can negatively impact little penguins (Costello & Colombelli-Négrel, 2023).…”
Section: Introductionmentioning
confidence: 99%